MAPPING THE WAVES AND OCEAN CURRENTS OF JAMBAK SAND BEACHES IN THE PADANG CITY OF WEST SUMATERA PROVINCE - Tamimy, Shabrina Mazaya; Galib, Musrifin; Zulkifli, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract             This research was conducted in July on Pasir Jambak beach and processing wave and flow data in August at the Office of the Meteorology and Geophysics Agency (BMKG) Center in DKI Jakarta This study aims to wave and flow using Windwaves 0.5 software and the effect on abrasion and accretion caused by ocean waves and currents. From the results of the study it can be seen that the wave height at tide is 2 m and at low tide is 1 m in July 2018. The waters of Pasir Jambak beach have tidal patterns 2 times and 2 times recede. First tide at 05.00-13.00 WIB, first recedes at 13.00-19.00 WIB, second tide is at 19.00-23.00 WIB, and second tide is at 23.00-05.00 WIB. Meanwhile, the current speed reaches 16cm / s at station I. At station II the current speed is 12 cm / s, and at station III 10 cm / s. As a result of high waves can cause the waters to experience abrasion and accretion Keyword: Mapping, Wave, Current, Jambak Sand Beaches, Abrasion, Acceretion